Report on the social security rights of short-term third-country national migrant workers - Vladimir Bogoeski; Zane Rasnača (European Trade Union Institute (ETUI), 2023)
This report provides an overview of the ways in which EU and EEA Member States have regulated their social security frameworks in relation to short-term thirdcountry national (TCN) migrant workers. It presents the result of an extensive mapping exercise carried out in 24 EU Member States, as well as Iceland and Norway, focussing on the relationship between migration and the social security coverage of different categories of short-term third-country national workers (for example, posted workers, intra-corporate transfers, seasonal workers, temporary agency workers, high-level professionals and self-employed). While every worker in the EU, in principle, is and should be covered by social security, certain groups of workers are subject to uncertainties and gaps in coverage. Third-country nationals who work in the EU for a short time are among the workers often subject to exclusions from social security coverage or not covered for certain risks. The individual country reports show that, as a general rule, employers who employ short-term third-country national migrant workers are supposed to pay social security and health care contributions as they do for regularly hired local workers. In the various jurisdictions this general rule is subject to various exceptions and restrictions. The internal and external fragmentation underlined by the variety of legal sources addressing social security issues, as well as the diversity of approaches potentially raises difficulties for the navigation of the respective systems. And while this seems justified in light of Member States' discretion in immigration and labour law, more legal certainty should be aimed for to better protect the workers experiencing this fragmentation and lack of coverage.
Keywords: 330; Migrant workers; Social security; EU countries; Arbeitsmigranten; Soziale Sicherheit; EU-Staaten